Typescript copies of the constitution and scheme of military organisation of the Irish Volunteers - Irish Volunteers (1914)
Photostat copy in a Bureau of Military History file of the 'Scheme of military organisation [of] the Irish Volunteers as published in The Irish Volunteer 26 Dec. 1914'. Typescript copy of the 'Constitution of the Irish Volunteers adopted at the First Irish Volunteer Convention'.
Keywords: Bureau of Military History, 1913-1921; Ireland -- History -- 1922-